Acute Respiratory Distress Syndrome: Role of Oleic Acid-Triggered Lung Injury and Inflammation - Cassiano Felippe Gonçalves-; Adriana Ribeiro Silva; Patrícia Burth; Mauro Velho Castro-Faria; Hugo Caire Castro- (Hindawi Limited, 2015)
Lung injury especially acute respiratory distress syndrome (ARDS) can be triggered by diverse stimuli, including fatty acids and microbes. ARDS affects thousands of people worldwide each year, presenting high mortality rate and having an economic impact. One of the hallmarks of lung injury is edema formation with alveoli flooding. Animal models are used to study lung injury. Oleic acid-induced lung injury is a widely used model resembling the human disease. The oleic acid has been linked to metabolic and inflammatory diseases; here we focus on lung injury. Firstly, we briefly discuss ARDS and secondly we address the mechanisms by which oleic acid triggers lung injury and inflammation.